Higher, Medium and Lower Order Thinking Skills in the Book al-‘Arabiyah Baina Yadaik - Amin, Nur Fadilah; Nasruni, Nasruni; Zainuddin, Nurkhamimi; Mutmainnah, Azzahratul (Institut Agama Islam Negeri Curup, 2023)
The ability to think in the cognitive domain is divided into three categories: low-, middle-, and high-level thinking skills. In learning Arabic, it is also required to be able to apply these three levels of thinking ability. Al-Arabiyah Baina Yadaik book is one of the books that is widely used in Indonesia in the process of learning Arabic, so this study seeks to reveal the three thinking skills in Al-Arabiah Baina Yadaik book, especially in book volume 1. The data collection method used is the documentation method, namely collecting and analyzing documents, both written documents, drawings, works, and electronics, with content analysis techniques as data analysis techniques. The results of this study indicate that the contents of the Book of Al-Arabiyah Baina Yadaik Volume 1 use more levels of low-level thinking skills, namely C1 and C2, while medium-level thinking skills only apply to 14 parts of tadribat. And at the level of higher-order thinking skills, there are only two parts to tadribat. This shows that the book Al-Arabiyah Baina Yadaik Volume 1 is very suitable for beginner students, especially for non-Arabic students.